(3JCjjO GdCacGQ dEJjGf GdWjhQ hfMhgG aj GdChcGQs - (3eMeO Hf Ydj Hf CMeO Hf Ydj Hf NeGQhjg Hf Whdhf GdOeTbqj GdUGdMj GdMfaj, TeS GdOjf , J (B953 (3g` s
(3ChdgG (B:s
(3hHYO agPG JYdjb SejJg HJCjjO GdGacGQ dEJjGf GdWjhQ hfMhgG ai GdGhcGQ gPG eSJfO ef PcQg ef GdYdeGA EJjGf GdWjQ hfMhgG ef GdhMhT hZjQgG ai GdGhcGQ s
(3BNQgG (B:s
(3djbY ajg GdeWQ ahbY ajg edcg hdjbY ajg GdTF GdefKhQ edcg dhbY ajg GfJgi s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B291s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdESdGejs